TREATMENT OF PREGNANT WOMEN WITH CONSTIPATION IN PMB YUNI WIDARYANTI, AMD. KEB SEMANDING VILLAGE, MAYANGAN JOMBANG - Dian Puspita Yani; Suyati Suyati; Arifa Retnowuni; Ashila Muhajir (Bajang Institute, 2021)
Constipation is actually mostly physiological, but if there is no assistance through midwifery care, it is possible that pathological conditions will occur. The purpose of this midwifery care is to provide midwifery care in accordance with the 7 steps of Varney's midwifery care. The method used in conducting midwifery care for Mrs. This “P” is Varney's 7 steps of midwifery care. Includes assessment of basic data, interpretation of basic data, identification of diagnoses and potential problems, determining immediate needs, developing a plan of care, implementation and evaluation that has been carried out in stages and procedures. The results to Mrs.